2011
DOI: 10.1074/jbc.m111.279174
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Human Natural Killer-1 (HNK-1) Sulfotransferase in the Biosynthesis of the GlcUA(3-O-sulfate)-Gal-Gal-Xyl Tetrasaccharide Found in α-Thrombomodulin from Human Urine

Abstract: Thrombomodulin (TM) is an integral membrane glycoprotein, which occurs as both a chondroitin sulfate (CS) proteoglycan (PG) form (␤-TM) and a non-PG form without a CS chain (␣-TM) and hence is a part-time PG. An ␣-TM preparation isolated from human urine contained the glycosaminoglycan linkage region tetrasaccharide GlcUA␤1-3Gal␤1-3Gal␤1-4xylose, and the nonreducing terminal GlcUA residue is 3-Osulfated. Because the human natural killer-1 sulfotransferase (HNK-1ST) transfers a sulfate group from 3-phosphoadeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Our structural analysis suggests that GlcAT-I, the sole enzyme identified for synthesis of the GAG linkage region to date, might be involved in the linkage type HNK-1 epitope on aggrecan in PNNs. Previous findings showing overexpression of GlcAT-I evoked HNK-1 immunoreactivity [ 46 ] and the sulfated linkage region was detected in human urine [ 56 , 57 ] further supports our hypothesis that GlcAT-I is the enzyme responsible for the synthesis of the unusual HNK-1 on aggrecan. However, directly demonstrating its involvement is difficult because GlcAT-I ( B3gat3 )-knockout mice show embryonic lethality at a very early stage [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our structural analysis suggests that GlcAT-I, the sole enzyme identified for synthesis of the GAG linkage region to date, might be involved in the linkage type HNK-1 epitope on aggrecan in PNNs. Previous findings showing overexpression of GlcAT-I evoked HNK-1 immunoreactivity [ 46 ] and the sulfated linkage region was detected in human urine [ 56 , 57 ] further supports our hypothesis that GlcAT-I is the enzyme responsible for the synthesis of the unusual HNK-1 on aggrecan. However, directly demonstrating its involvement is difficult because GlcAT-I ( B3gat3 )-knockout mice show embryonic lethality at a very early stage [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Actually, we and Dr. Sugahara's group demonstrated that HNK-1ST can use a glycosaminoglycan linkage tetrasaccharide on thrombomodulin as an acceptor substrate to form an unusual sulfated structure (Fig. 1B) [46,47]. The sulfated linkage region on thrombomodulin was indeed identified in human urine, SO 4 -3GlcAβ1-3Galβ1-3Galβ1-4Xyl [48], and a non-elongated form of proteoglycan is known to exist as a part-time proteoglycan [49,50].…”
Section: Biosynthetic Enzymes Of Hnk-1 Glycanmentioning
confidence: 96%
“…A terminal sulfated GlcUA linked to a sulfated GalNAc residue was observed the CS/DS from HCC70 cells after chondroitinase AC-I and -II degradation. It was not possible to assign the position of the sulfate group on GlcUA; however, human natural killer-1 sulfotransferase (HNK-1ST), the enzyme responsible for the 3-Osulfation of the truncated linkage region of ␣-thrombomodulin, may be involved (55). Although terminal 3-O-sulfation of GlcUA in mammals has hitherto only been observed in this context, it is noteworthy that recombinant HNK-1ST has shown activity also toward the terminal GlcUA residues in chondroitin of various lengths.…”
Section: Lc-ms/ms Of Xyloside-primed Chondroitin/dermatan Sulfatementioning
confidence: 99%